A novel report on phthalates levels in Biscayne Bay surface waters and drinking water from South Florida. (July 2022) - Cui, Danni; Ricardo, Melissa; Quinete, Natalia
Abstract: In this research, we have developed and validated a modified version of the U.S.EPA method 506 using a liquid-liquid extraction method followed by gas-chromatography mass spectrometry analysis to assess the occurrence and spatial and seasonal variation of six phthalates (di(2-ethylhexyl) phthalate-DEHP, dibutyl phthalate-DBP, butyl benzyl phthalate-BBP, diethyl phthalate-DEP, dimethyl phthalate-DMP, and di-n-octyl phthalate-DOP) in surface and tap waters from South Florida, collected during the wet and dry seasons. The most frequently detected phthalate was DEHP, with concentrations up to 1.56 μg/L in surface water. Higher DEHP concentrations were observed in tap water during the wet season, which aligns with the higher temperature during the summer months facilitating leaching from plastic materials. Preliminary ecological and human health risk assessments suggested low hazard risk based on concentrations observed in tap and surface waters, respectively. PAEs could however still constitute a great concern to sensitive marine species, including early stages organisms and coral reefs. Highlights: Phthalates were reported for the first time in South Florida's surface and tap waters. DEHP was the predominant PAE compound detected with the highest concentrations. PAEs levels might be related with plastic wastes/debris, wastewater intrusion, and urban runoffs. No clear spatial or seasonal variations of PAEs were observed in the water samples. Low ecological or human health risk observed are likely underestimated.